A Study on Optical Parameters of Ge-Se-Te Thin Film for Optical Storage Devices - Agarwal, Manuj Kumar; Saxena, Manish; Gupta, Shilpa (International Journal of Computer Sciences and Engineering, 2018)
The chalcogenide glasses have recently been investigated intensively because of their promising technological applications in reversible phase change optical recording. Recently, there is a trend of using amorphous materials, rather than carefully prepared crystalline semiconductors, in much needed investigation of such chalcogenide based materials. The present study examines the impact of germanium (Ge) content variation on the optical properties of GexSe50Te50-x (x = 10, 20, 30, 40 at %) based thin films. The optical absorption estimations were performed at room temperature with the change in wavelength. Numerous optical constants were also studied for the concentrated thin films using the optical absorption information in transmission spectra. It was observed that the optical absorption mechanism follow the rule of the allowed direct transition. The theoretical band gap was found to decrease as the Ge content (%) increases from 10 to 40 at %. This outcome was clarified regarding the compound bond approach and hence shows usefulness for optical recording devices.